2017
DOI: 10.1186/s12903-017-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in unmet dental care needs among South Korean adults

Abstract: BackgroundThe current public health research agenda was to identify the means to reduce oral health inequalities internationally. The objectives of this study were to provide evidence of inequality in unmet dental needs and to find influencing factors attributable to those among South Korean adults.MethodsPooled cross-sectional data from the fourth Korean National Health and Nutrition Examination Survey (2007–2009) on 17,141 Korean adults were used. Demographic factors (sex, age, and marital status), socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 34 publications
5
59
2
3
Order By: Relevance
“…Unmet dental care needs are problematic and are a global public health concern. Previous research on unmet dental care needs has suggested that age, race, and socioeconomic factors are barriers of dental care [ 4 , 5 ]. In particular, social determinants of health are thought to be the root cause of unmet dental care needs and medical problems [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unmet dental care needs are problematic and are a global public health concern. Previous research on unmet dental care needs has suggested that age, race, and socioeconomic factors are barriers of dental care [ 4 , 5 ]. In particular, social determinants of health are thought to be the root cause of unmet dental care needs and medical problems [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many places that do not offer dental coverage for adults with Medicaid force patients to rely on emergency departments for dental treatments which are not equipped to provide preventive and specialized dental care [ 7 ]. Provider discontinuity [ 9 ], income level, normative treatment needs, and self-reported oral health status [ 5 ] are other characteristics that have been found to be associated with people with unmet dental needs as well.…”
Section: Introductionmentioning
confidence: 99%
“…First, households with a female head have lower income levels and consequently, are less likely to pay for health services, especially expensive dental services. As shown in a study performed in Indonesia and a study by Kim et al in South Korea, due to economic difficulties, the chance of having unmet dental care needs is higher in women (40,41). Second, women are more interested in their health than men and they use preventive services more than dental care services (39).…”
Section: Discussionmentioning
confidence: 97%
“…The "Oral Health Questionnaire for Adults" has been used in national surveys in many countries 17,18 . We used the Serbian version of the questionnaire "Oral Health Questionnaire for Adults" in our study according to recommendations of WHO 4 .…”
Section: Discussionmentioning
confidence: 99%